Antibacterial effect and healing potential of topically applied licorice root extract on experimentally induced oral wounds in rabbits - Venus Dilshad Najeeb; Ali Sultan Al-Refai (Wolters Kluwer Medknow Publications, 2015)
Background and Objectives: Evidence has accumulated linking the effects of licorice for the treatment of many diseases. The objectives of this study were to evaluate the antibacterial action of licorice root extract against Staphylococcus aureus and to study its healing potential on the experimentally induced oral wounds in the rabbit's cheek mucosa. Materials and Methods: Different concentrations of licorice root extract were prepared and their antibacterial activities against S. aureus determined by disk diffusion method. The wound had been created using of biopsy punch at the right cheek mucosa of the rabbit. In the study group, these wounds were irrigated with 1 ml of 60 g/100 ml of licorice root extract twice daily. Seven rabbits from the control and the study group were sacrificed in the 3 rd and 6 th day of the experiment, and biopsies were taken for histological observations of the wounds. Results: There was no sensitivity of S. Aureus to different concentrations of licorice extract. The histological features of oral wounds in the study group showed satisfactory healing potential after twice daily irrigation with 60 g/100 ml of licorice root extract in comparison to control group. Conclusions: Different concentrations of licorice root extract has no antibacterial action against S. aureus, but licorice can shorten the healing time of the induced oral mucosal wounds in rabbits.